Formal Mixture in the Sonata-Form Movements of Middle- and Late-Period Beethoven - MacKay, James (Intersections, 2010)
Modal mixture is defined as a local colouration of a diatonic progression by borrowing tones or chords from the parallel major or minor tonality. In his efforts to expand tonal resources, Beethoven took this technique further: he borrowed large-scale tonal processes from a composition’s parallel tonality, a technique that I term formal mixture. After tracing its origin to certain works by J. S. Bach, C. P. E Bach, Domenico Scarlatti, and Joseph Haydn, I demonstrate how Beethoven built upon his predecessors’ use of the technique throughout his career, thereby expanding and diversifying the tonal resources of late classical era sonata forms.